Vilém Flusser e a ditadura militar os posicionamentos do autor e a dimensão política de seu pensamento a partir da correspondência com José Bueno na década de 1970 - Silva, Tiago da Mota e (2023)
The present thesis analyzes the political positioning of Vilém Flusser based on the correspondence that the philosopher maintained with his friend, José Bueno, mainly throughout the 1970s. In addition to this set of letters, the research also investigated other exchanges between the author and personalities who were part of the circle of conservative intellectuals at the Brazilian Institute of Philosophy (IBF), such as Augusto Becker, Luigi Bagolini and Miguel Reale, and with the artist Antônio Henrique Amaral, as well as his unpublished essays and courses. Thanks to this collection of materials, all of which are part of the Vilém Flusser Archive in São Paulo, it became possible to explore subjects that remain ambiguous in Flusser's published work: his position regarding the Brazilian military dictatorship, his perspective on the socialist experience, the role that Marxism plays in his thinking, and the evidence of a crisis in the ways of life produced by the West. As a result, one can conjecture how the author politically disagreed with his friends from the IBF, especially in their reactionary and pro-military opinions. Furthermore, this material also allows revisiting Flusser's Communicology -- his proposal for a Theory of Communication -- to study the political dimension of his thinking. Thus, we arrive at his original notion of politics, one that would have been formulated based on his understanding of Communication. In support of these arguments, other essays by researchers of Flusser's life and work were mentioned, such as Alex Heilmair, Diogo A. Bornhausen, Norval Baitello Junior, Rainer Guldin and Rodrigo Novaes, in addition to studying the published books of the Czech-Brazilian philosopher